2016
DOI: 10.1051/0004-6361/201528005
|View full text |Cite
|
Sign up to set email alerts
|

VEGA/CHARA interferometric observations of Cepheids

Abstract: Context. The B-W method is used to determine the distance of Cepheids and consists in combining the angular size variations of the star, as derived from infrared surface-brightness relations or interferometry, with its linear size variation, as deduced from visible spectroscopy using the projection factor. The underlying assumption is that the photospheres probed in the infrared and in the visible are located at the same layer in the star whatever the pulsation phase. While many Cepheids have been intensively … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…However, a disagreement is still found between the interferometric and the infrared surface-brightness approaches (and their respective projection factors) in the case of δ Cep , while an agreement is found for the long-period Cepheid ℓ Car (Kervella et al 2004b). This suggests that the p-factors adopted in these approaches might be affected by something not directly related to the projection factor itself but rather to other effects in the atmosphere or close to it, such as a static circumstellar environment (Nardetto et al 2016). However, it is worth mentioning that the two methods currently provide absolutely the same results in terms of distances.…”
Section: Resultsmentioning
confidence: 99%
“…However, a disagreement is still found between the interferometric and the infrared surface-brightness approaches (and their respective projection factors) in the case of δ Cep , while an agreement is found for the long-period Cepheid ℓ Car (Kervella et al 2004b). This suggests that the p-factors adopted in these approaches might be affected by something not directly related to the projection factor itself but rather to other effects in the atmosphere or close to it, such as a static circumstellar environment (Nardetto et al 2016). However, it is worth mentioning that the two methods currently provide absolutely the same results in terms of distances.…”
Section: Resultsmentioning
confidence: 99%
“…Envelopes around Cepheids have been discovered by longbaseline interferometry in the K-Band with VLTI and CHARA Mérand et al 2006), and four Cepheids CSEs have been observed in the N band with VISIR and MIDI (Kervella et al 2009;Gallenne et al 2013) and one with NACO in the near-IR (Gallenne et al 2011). The presence of a motionless Hα absorption component using high-resolution spectroscopy around l Car (Nardetto et al 2008) has also been attributed to a CSE, and, recently, a CSE was detected in the visible domain with the VEGA/CHARA facility around δ Cep (Nardetto et al 2016). These various studies determined a CSE radius of 2.…”
Section: Introductionmentioning
confidence: 95%
“…Characterizing these CSEs, and in particular their radial brightness profile in several spectral bands will enable one to unbias the period-luminosity relation. Recently, δ Cep was observed with the VEGA/CHARA instrument and an unexpected visible CSE contributing to 7% to the total flux was discovered [20]. Many more visible CSEs can be discovered with a more sensitive visible instrument.…”
Section: A and B Stars Binarity Below 30 Aumentioning
confidence: 99%